2015
DOI: 10.2147/dddt.s72716
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-inflammatory potential of cinnamate-zinc layered hydroxide in lipopolysaccharide-stimulated RAW 264.7 macrophages

Abstract: BackgroundCinnamic acid (CA) is a phytochemical originally derived from Cinnamomum cassia, a plant with numerous pharmacological properties. The intercalation of CA with a nanocarrier, zinc layered hydroxide, produces cinnamate-zinc layered hydroxide (ZCA), which has been previously characterized. Intercalation is expected to improve the solubility and cell specificity of CA. The nanocarrier will also protect CA from degradation and sustain its release. The aim of this study was to assess the effect of interca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Cinnamic acid alone and several CA derivatives demonstrated the ability to influence the activity or expression of the pro-inflammatory transcription factor NF-κB in previous studies [15,33]. The effect of N-arylcinnamamide derivatives with the modified cinnamyl phenyl ring on NF-κB activity was studied by Chen et al [23] as well as by Jan et al [34], but the effect of derivatives with the unchanged cinnamyl moiety is described here for the first time.…”
Section: Inhibition Of Nf-κb Activity and Cell Signaling In Vitromentioning
confidence: 76%
“…Cinnamic acid alone and several CA derivatives demonstrated the ability to influence the activity or expression of the pro-inflammatory transcription factor NF-κB in previous studies [15,33]. The effect of N-arylcinnamamide derivatives with the modified cinnamyl phenyl ring on NF-κB activity was studied by Chen et al [23] as well as by Jan et al [34], but the effect of derivatives with the unchanged cinnamyl moiety is described here for the first time.…”
Section: Inhibition Of Nf-κb Activity and Cell Signaling In Vitromentioning
confidence: 76%
“…The report has shown that a high amount of prostaglandins PGE2, cytokines, and NO are secreted by the macrophages and other stimulated inflammatory cells. [60][61][62][63][64] In the male reproductive tract, nitric oxide synthase (NOS) has been found in the testes, epididymis, and vascular endothelial cells. NO at the physiologic level improves sperm motility and function, but excessive NO in sperm causes detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of d -galactose also led to increased concentration of Nitric oxide. A high amount of prostaglandins PGE2, cytokines, and nitric oxide (NO) are secreted by the macrophages and other stimulated inflammatory cells [ 25 ]. In the male reproductive tract, nitric oxide synthase (NOS) has been found in the testes, epididymis, and vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%